Inhibition of CXCR4–CXCL12 chemotaxis in melanoma by AMD11070 - O'Boyle, G (Nature Publishing Group, 2013)
BACKGROUND: Despite intensive research and novel adjuvant therapies, there is currently no cure for metastatic melanoma. The chemokine receptor CXCR4 controls metastasis to sites such as the liver; however, the therapeutic blockade with the existing agents has proven difficult. METHODS: AMD11070, a novel orally bioavailable inhibitor of CXCR4, was tested for its ability to inhibit the migration of melanoma cells compared with the commonly described antagonist AMD3100. RESULTS: AMD11070 abrogated melanoma cell migration and was significantly more effective than AMD3100. Importantly for the clinical context, the expression of B-RAF-V600E did not the affect the sensitivity of AMD11070. CONCLUSION: Liver-resident myofibroblasts excrete CXCL12, which is able to promote the migration of CXCR4-expressing tumour cells from the blood into the liver. Blockade of this axis by AMD11070 thus represents a novel therapeutic strategy for both B-RAF wild-type and mutated melanomas.